Monitoring the oxidative stability of virgin coconut oil during oven test using chemical indexes and FTIR spectroscopy. - Abdul Rohman,; Che Man, Yaakob; Ismail, Amin; Hashim, Puziah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
This study was conducted to evaluate the oxidative stability of virgin coconut oil (VCO) during oven test. VCO with and without antioxidants were subjected to oven test at 63°C over a 40 day-storage. The chemical parameters namely peroxide value (PV) and specific absorptivity of conjugated dienes (CDs) and conjugated trienes (CTs) were used to asses VCO stability. VCO samples treated with the mixture of butylated hydroxyanisole and butylated hydroxytoluene (BHA/BHT of 200 mg/kg) and citric acid (CA, 100 mg/kg) have lower PVs than control (VCO without antioxidants) and other treatments. The specific absorbtivities of CDs and CTs of VCO were also decreased due to the addition of antioxidants. In addition, Fourier transform infrared (FTIR) spectroscopy was used to monitor the peak changes during the thermal oxidation. The prominent peak change observed during thermal oxidation of VCO was at frequency 1739 cm-1 which corresponded to the carbonylic compounds (esters, aldehydes, ketones, lactones) resulted from the hydroperoxide decompositions during oven test